Analisis Risiko Keselamatan dan Kesehatan Kerja Menggunakan Metode Matrik Dan FMEA - Falensius Mendrofa; Romulo P Aritonang (JEMA: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The concept of Occupational Safety and Health (OSH) focuses on creating a hazard-free work environment. To achieve this goal, a systematic method is needed to identify and manage risks. One popular method is Failure Mode and Effect Analysis (FMEA). FMEA works by breaking down a work process into smaller steps, then identifying potential failures at each step. After that, the impact of each failure is evaluated. Thus, we can prioritize the most effective preventive measures. In the case of PTPN-2 mill, the application of FMEA has successfully identified various potential hazards, such as injuries from falling or being punctured by sharp objects. In response, the company has equipped workers with appropriate Personal Protective Equipment (PPE), significantly reducing the risk level.